2009
DOI: 10.1007/s00246-009-9594-z
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Calcification of Giant Coronary Artery Aneurysm of an 11-Year-Old Child with History of Kawasaki Disease

Abstract: We present radiographic images of ring-calcification of a giant aneurysm of the left main coronary artery in a child, 7 years after the initial diagnosis of Kawasaki disease, as well as acute medical management and surgical bypass of the obstructed left anterior descending coronary artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Previous studies have found that vasoactive factors, including vascular endothelial growth factors, nitric oxide, and platelet-derived growth factors, etc., may initiate the migration and proliferation of SMCs, as well as control the vascular permeability of KD progression [1-5, 32, 33]. Accumulating clinical data has further indicated that KD patients with large aneurysms may have an increased incidence of coronary artery calcification formation [27][28][29]. Moreover, it has been suggested that coronary artery calcification may be one of the sequelae of severe vasculitis occurring in acute KD patients [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have found that vasoactive factors, including vascular endothelial growth factors, nitric oxide, and platelet-derived growth factors, etc., may initiate the migration and proliferation of SMCs, as well as control the vascular permeability of KD progression [1-5, 32, 33]. Accumulating clinical data has further indicated that KD patients with large aneurysms may have an increased incidence of coronary artery calcification formation [27][28][29]. Moreover, it has been suggested that coronary artery calcification may be one of the sequelae of severe vasculitis occurring in acute KD patients [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating clinical data has further indicated that KD patients with large aneurysms may have an increased incidence of coronary artery calcification formation [27][28][29]. Moreover, it has been suggested that coronary artery calcification may be one of the sequelae of severe vasculitis occurring in acute KD patients [27][28][29]. The clinical symptoms of vascular calcification in KD patients has already been demonstrated, however its mechanism is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…711 We did not have chest radiographs on the subjects in this study, and hence were unable to compare data between chest radiographs and CT. Some of the subjects in this study had dense calcification that would be expected to be apparent on chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…The LMA in children is often found in Kawasaki or Takayasu disease. It may also be associated with other cardiac defects such as postponement of the main arteries, or tetralogy of Fallot [7, 8]. A definitive diagnosis can rarely be made.…”
Section: Introductionmentioning
confidence: 99%